Tailoring caustics in high-harmonic generation with phase-controlled multi-colour fields - Mitra, Sambit; Biswas, Shubhadeep; Schötz, Johannes; Förg, Benjamin; Okell, William; Kavuri, Gautam A.; Högner, Maximilian; Pupeza, Ioachim; Wnuk, Pawel; Kling, Matthias Friedrich (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
High harmonic generation (HHG) using intense laser pulses has long proven to be an extremely reliable source of high-energy, ultrashort (down to few tens of attoseconds) and coherent light radiation. This has promoted HHG as the tool of choice for numerous scientific applications. As understood by the three-step model, HHG is a highly nonlinear process which is strongly dependent on the classical electric field shapes of the driving laser pulse [1]. Thus, a common approach to control the HHG spectrum has been by modifying this electric field. Previous works in this direction primarily focused on weak perturbative approaches to either modify the ionization probability, suppress electron re-scattering by slight modification of the electron trajectory or use macroscopic manipulation of the generating medium. Our work focuses on a significantly less explored area [2,3], where the driving electric field structure is very strongly modified by a secondary field. This causes drastic changes in re-colliding electron trajectories, leading to highly modified HHG spectra as a function of their relative phase.
CRIS-Team Scopus Importer:2023-04-20